2010
DOI: 10.1016/j.copbio.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biotechnological approaches for biofuel crop improvement

Abstract: Research and development efforts for biofuel production are targeted at converting plant biomass into renewable liquid fuels. Major obstacles for biofuel production include lack of biofuel crop domestication, low oil yields from crop plants as well as recalcitrance of lignocellulose to chemical and enzymatic breakdown. Researchers are expanding the genetic and genomic resources available for crop improvement, elucidating lipid metabolism to facilitate manipulation of fatty acid biosynthetic pathways and studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 55 publications
(60 reference statements)
2
54
0
1
Order By: Relevance
“…Inclusion of monolignol substitutes, such as feruloylquinic acid, methyl caffeate, or caffeoylquinic acid with normal monolignols could considerably suppress lignin formation and substantially improve cell wall hydrolysis and fermentation (Grabber et al, 2010). Besides lignin, hemicellulose (including xylan, glucuronoxylan, arabinoxylan, glucomannan, and xyloglucan) also contributes to plant cell wall recalcitrance (Vega-Sanchez & Ronald, 2010). It has been demonstrated that modification of hemicellulose could help overcome biomass recalcitrance.…”
Section: Genetic Improvement Of Biofuel Yieldmentioning
confidence: 99%
See 4 more Smart Citations
“…Inclusion of monolignol substitutes, such as feruloylquinic acid, methyl caffeate, or caffeoylquinic acid with normal monolignols could considerably suppress lignin formation and substantially improve cell wall hydrolysis and fermentation (Grabber et al, 2010). Besides lignin, hemicellulose (including xylan, glucuronoxylan, arabinoxylan, glucomannan, and xyloglucan) also contributes to plant cell wall recalcitrance (Vega-Sanchez & Ronald, 2010). It has been demonstrated that modification of hemicellulose could help overcome biomass recalcitrance.…”
Section: Genetic Improvement Of Biofuel Yieldmentioning
confidence: 99%
“…A major bottleneck for conversion of lignocellulosic biomass to simple sugars (saccharification), to be subsequently converted by microorganisms into ethanol or other products, is the recalcitrance to enzymatic saccharification (Chen & Dixon, 2007;Lionetti et al, 2010). Recalcitrance is mainly due to the heterogeneity and molecular structure of lignocellulose where cellulose is arranged into a network of tight, inter-chain hydrogen bonds that form a crystalline core of microfibrils, embedded in a matrix of hemicellulosic polysaccharides that are covalently linked to lignin, a highly complex aromatic polymer (Vega-Sanchez & Ronald, 2010). Lignin contributes to biomass recalcitrance and consequently increases the costs associated with conversion (Simmons et al, 2010;Vega-Sanchez & Ronald, 2010).…”
Section: Recalcitrance Of Biomass For Biofuel Productionmentioning
confidence: 99%
See 3 more Smart Citations